ANALISA SISTEM JARINGAN IRIGASI TERSIER DESA CITARIK KECAMATAN PELABUHAN RATU KABUPATEN SUKABUMI - Mulyadi, Mulyadi; Sitanggang, Ansadilla Niar (Universitas 17 Agustus 1945 Jakarta, 2021)
A very important factor in increasing agricultural production is irrigation. With an irrigation system, we can irrigate plants in the right amount and time, so that plants can grow well and can produce optimally. In planning an irrigation system, the first thing that needs to be done is a hydrological analysis including the water demand in the fields (GFR), the demand for water intake (DR), the clean water requirement in the fields (NFR) as well as the water availability factor, where the amount of water demand will determine the amount of water needed. irrigation building planning. In this study, rainfall analysis was carried out, Rainfall Data Consistency Test, Mainstay Rainfall and Effective Rainfall, Calculation of Planting Water Needs, Rotational Water Distribution System and Rotational Hours. water distribution system in the irrigation area of Citarik Village, Pelabuhan Ratu District, Sukabumi Regency. The results of the research show that the water needs for plants have been met with the results of the calculation of the planned discharge with a planned q of 1.776 lt/sec/ha with an area of 150 ha and irrigation efficiency 60% = 1.776/0.60 = 2.961 lt/sec/ha x 150 ha = 444.22 lt/sec. The distribution of water on a rotational basis is carried out by classifying the rice fields into three groups and three hours of rotationKeywords: rainfall, discharge, irrigation channel